Investigation into the effect of shock acceleration characteristics on the performance of a proposed MEMS inertial switch. (1st December 2016) - Cao, Yun; Xi, Zhanwen; Wang, Jiong; Nie, Weirong; Yu, Pingxin
Abstract : Rapid response is required for many applications of a micro‐electro‐mechanical system (MEMS) inertial switch device. To achieve a rapid response and have a long contact time, the influence of applied acceleration characteristics on the performance of a proposed MEMS inertial switch, such as response time and contact time, was investigated. The results indicate that the response time of the switch gradually decreases, but the contact time rapidly increases first and then smoothly increases, as the acceleration amplitude increases and the pulse width is a constant. Furthermore, the broadening of acceleration pulse width will result in a sudden increase of response time. For the sake of rapid response, the switch should be used within a limited pulse width range of 0 < t 0 < 5.78 π / ωn 1, as the applied acceleration amplitude is 1.2 times of the acceleration threshold. The fabricated switches were tested by a shock test device. The test results are in good agreement with the simulation results.